Kinerja Karyawan melalui Loyalitas, Komunikasi, Dan Kompensasi Kerja pada CV. Batik Sumber Arafat Tanjung Bumi, Bangkalan - Mun'im, Abd.; Kuswinarno, Mudji (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
CV. Batik Sumber Arafat Tanjung Bumi, Bangkalan is one of the batik business places in Tanjung Bumi District, Bangkalan that is the largest batik area in Bangkalan. This business has been since 2004 and provides all types of Madurese batik such as gentongan (*Madurese), writing cotton, silk, stamping and printing. As the one of the batik businesses in Tanjung Bumi, CV. Batik Sumber Arafat must have good employees performance, starting from employees work loyalty, communication, and compensation. The aims of this study are to determine and analyze the effect of loyalty, communication and compensation on employees performance, partially and simultaneously. It uses the quantitative methods with surveys the employees as much as 43 respondents. Using the multiple regression analysis, the results showed that (1) loyalty has a positive and significant effect on employees performance as 0.346; (2) communication has no effect on employees performance as 0.025; (3) compensation has a positive and significant effect on employees performance as 0.353; (4) loyalty, communication and compensation effect on employees performance simultaneously as 54%.